Insights on nitrate respiration by Shewanella - Chen, Ying; Wang, Fengping (Frontiers in Marine Science, 2015)
Shewanellae are well known for their ability to utilize a number of electron acceptors and are therefore considered to have important roles in element cycling in the environment, such as nitrogen cycling through dissimilatory nitrate reduction to ammonia (DNRA) and denitrification. Possessing two periplasmic nitrate reductase systems (NAP-α and NAP-β) is a special trait of the Shewanella genus, and both enzymes are likely to provide selective advantage to the host. This review relates the current knowledge and aspects of the nitrate respiration system of Shewanella. Specifically, the potential physiological functions and regulation mechanisms of the duo-NAP system are discussed in addition to the evolution of anaerobic respiration systems of Shewanella.